Problems and solutions outside protected areas - John Waithaka (Pachyderm)
Only the the summary of the presentation is published. Outlines some of the new concepts and approaches to wildlife management in order to encure conservation as they are being explored in Kenya. Notes the land use conflict between a growing human populations' land needs with respect to the presence of animals found outside conservation areas.